Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1038/nm0297-189
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 mediates T cell-dependent regulation of tumor necrosis factor-α production in rheumatoid arthritis

Abstract: Tumor necrosis factor-alpha occupies a central role in rheumatoid arthritis (RA) pathogenesis. We now report that interleukin-15 (IL-15) can induce TNF-alpha production in RA through activation of synovial T cells. Peripheral blood (PB) T cells activated by IL-15 induced significant TNF-alpha production by macrophages via a cell-contact-dependent mechanism. Freshly isolated RA synovial T cells possessed similar capability, and in vitro, IL-15 was necessary to maintain this activity. IL-15 also induced direct T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
369
2
9

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(395 citation statements)
references
References 36 publications
12
369
2
9
Order By: Relevance
“…Expression of IL-15 was demonstrated not only in macrophages but also in endothelial cells and fibroblastlike synoviocytes, and the concentration of IL-15 in synovial fluids was shown to be elevated in RA patients [22][23][24][25][26]. It was also shown that IL-15 induced TNF-a production from macrophages through activation of synovial T cells in RA patients [27]. These findings suggest an involvement of IL-15 in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 79%
“…Expression of IL-15 was demonstrated not only in macrophages but also in endothelial cells and fibroblastlike synoviocytes, and the concentration of IL-15 in synovial fluids was shown to be elevated in RA patients [22][23][24][25][26]. It was also shown that IL-15 induced TNF-a production from macrophages through activation of synovial T cells in RA patients [27]. These findings suggest an involvement of IL-15 in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 79%
“…38 This cytokine induced TNF-a production by synovial fluid T cells. 39 IL-15 is also a potent activator of NK cell function, stimulating proliferation, cytokine secretion and cytotoxicity. 40 In addition, recent data suggest that the action of certain drugs effective in the treatment of RA (antimalarials and cyclosporin A) could be attributable to effects on NK cell activation.…”
Section: Fccriiia Allelic Polymorphisms In Ramentioning
confidence: 99%
“…Thus, IL-15 may influence both Th1 and Th2 cells. Aberrant IL-15 expression was observed in patients with inflammatory autoimmune disease, such as rheumatoid arthritis (18,19) and inflammatory bowel diseases (20,21), suggesting that IL-15 is involved in the pathogenesis of inflammatory disease. However, the potential role of IL-15 in allergic responses in vivo remains to be elucidated.…”
Section: Overexpression Of Il-15 In Vivo Enhancesmentioning
confidence: 99%